Interactive responses of Quercus suber L. seedlings to light and mild water stress: effects on morphology and gas exchange traits - Puértolas, J; Pardos, M; Jiménez, M D (Annals of Forest Science, 2008)
• The combined eﬀect of water stress and light on seedlings of forest species is a key factor to determine the best silvicultural and aﬀorestation practices in the Mediterranean area. • The aims of this work was (1) to determine the optimal light level for the early development of cork oak seedlings under mild water stress and (2) to test if the combined eﬀect of water stress and light followed the trade-oﬀ, the facilitation or the orthogonal hypothesis. • Shade reduced instantaneous photosynthetic rates and water use eﬃciency in cork oak. However, seedlings grown under moderate shade (15% of full sunlight) were capable to accumulate similar amount of biomass than those grown under more illuminated environments by increasing their speciﬁc leaf area. Absolute diﬀerences in net photosynthesis between light treatments were higher in well watered than in water stressed seedlings. However, the impact of both factors on overall growth was orthogonal. • We concluded that cork oak development is impaired under deep shade (5% of full sunlight) but it can be optimal under moderate shade (15% of full sunlight) even under moderate water stress. Implications of these patterns on regeneration, cultivation and aﬀorestation of cork oak are discussed.
Keywords: Cork oak; foliar anatomy; photosynthesis rate; shade acclimation; water use effciency

Variación en la actividad del fotosistema ii de plantas de alcornoque (Quercus suber L.) SOMETIDAS A ESTRÉS HÍDRICO MODERADO Y BAJO DISTINTOS NIVELES DE RADIACIÓN - Jiménez, M D; Pardos, M; Aranda, I; Puértolas, J; Pardos, J A (IV Congreso Forestal Español, 2005)
Se estudió el efecto conjunto de la luz y la disponibilidad hídrica sobre la actividad del fotosistema II (PSII) en plantas de alcornoque (Quercus suber L.) cultivadas en vivero. Se consideraron cuatro niveles de luz (66-70% , 44-50%, 13.5-16% y 5-6%, con respecto a pleno sol) y dos de riego. La mitad de las plantas se regaron a capacidad de campo dos veces por semana (R+: 25-35% de humedad en el sustrato, medido con TDR) y la otra mitad se sometió a dos ciclos de sequía de 51 y 38 días, respectivamente (R-: hasta alcanzar una humedad en el sustrato del 7-10%). Las mediciones se realizaron al amanecer, mediodía y tarde, en cuatro fechas en hojas adaptadas a la oscuridad, empleándose un fluorómetro. Para todos los tratamientos, Fv/Fm presentó los valores más altos al amanecer, disminuyó al mediodía, y experimentó una ligera recuperación por la tarde en los tratamientos de máximo sombreo para la medición del 23 de Julio. Fv/Fm decreció a lo largo del ensayo (al mediodía y por la tarde) hasta alcanzar un mínimo tras finalizar el primer ciclo de sequía.. El riego afectó positivamente la relación Fv/Fm al amanecer solamente en la última medición del primer ciclo. Asimismo se detectó un efecto positivo en los niveles de luz intermedios (13.5% y 16%). Al mediodía y por la tarde, la eficiencia fotoquímica del PSII fue mayor con niveles de luz inferiores al 16%. La eficiciencia cuántica del fotosistema II mostró dos repuestas a las altas radiaciones una caída diaria al mediodía, como un mecanismo de fotoproctección en las horas de mayor radiación y una disminución a lo largo del tiempo que duró el ensayo. El tratamiento de riego no provocó cambios en la eficiencia cuántica del PSII, salvo en una fecha, coincidiendo con la máxima demanda evaporativa. Los tratamientos mayores de luz (>44%) provocaron una pérdida de la eficiencia cuántica del PSII.
Keywords: eficiencia fotoquímica máxima del PSII (Fv/Fm); fluorescencia máxima; fluorescencia variable

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M; Royo, A; Gil, L; Pardos, J A (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)